Healthy Eating: Fluids - Linda B. Bobroff; Luisa Oliver-Cordero; Emily Minton (EDIS)
More than one-half of an adult human body weight is water. Water brings nutrients to the cells in our bodies and removes waste. Our bodies cannot function without an adequate water supply. This revised 2-page fact sheet was written by Linda B. Bobroff, Luisa Oliver-Cordero, and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, October 2012.